2021
DOI: 10.1209/0295-5075/ac0dfb
|View full text |Cite
|
Sign up to set email alerts
|

Stellar age dependence of the nonextensive magnetic braking index: A test for the open cluster αPer

Abstract: Using a generalized function of the stellar spin-down law, we investigate the age dependence of the magnetic braking index (q). Our survey includes 9 open clusters aged lower than 1 Gyr and ranged in mass from 0.7 to 1.1M . Our aim is to verify the time behaviour of the nonextensive braking index q which brings the cumulative distribution of the rotational velocities of the stars of the youngest cluster (αPer) taken at the future age of an older cluster. As a result, the q-index is calculated over time t−tαPer… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…At present, some literatures focus on metallicities, age spread, fast rotating, the amplitude of photometric variability and so on, which can affect the age determination of star clusters. Some comments can be found in the papers (e.g., Gossage et al 2018;Catelan 2018;Wang et al 2020a;Anders et al 2021;de Freitas 2021). Li & Han (2008) investigated the effects of binary interactions on age and metallicity of star clusters based on the isochrone and spectral energy distribution fittings, but its results were mainly obtained from the theoretical side on account of the limitation of computing ability.…”
Section: Introductionmentioning
confidence: 99%
“…At present, some literatures focus on metallicities, age spread, fast rotating, the amplitude of photometric variability and so on, which can affect the age determination of star clusters. Some comments can be found in the papers (e.g., Gossage et al 2018;Catelan 2018;Wang et al 2020a;Anders et al 2021;de Freitas 2021). Li & Han (2008) investigated the effects of binary interactions on age and metallicity of star clusters based on the isochrone and spectral energy distribution fittings, but its results were mainly obtained from the theoretical side on account of the limitation of computing ability.…”
Section: Introductionmentioning
confidence: 99%
“…Modeling the stellar magnetic braking index. -First of all, the present paper is the second one (Paper I: [22]) of a series of three papers which brings a new approach to the non-extensive magnetic braking as a determining factor for understanding the delicate mechanisms that control the spin-down of stars in different luminosity classes. By using the equation proposed in [22] to describe the behavior of the rotational velocity, we have that:…”
mentioning
confidence: 99%
“…As cited in Paper I, the non-extensive formalism reveals to be a powerful theory for studying stellar systems, among them open clusters and field stars as will be seen here. Several studies (e.g., [13,22]) have shown that the stellar rotational braking mechanism can be explained by investigating the behavior of the entropic index q. As a result, de Freitas and De Medeiros [13] suggested that increasing index q behavior between the saturated (q = 1) and unsaturated (1 < q < 3) magnetic field regimes as a function of spectral type may explain the process of magnetic transition that occurs in the stellar dynamo dynamics.…”
mentioning
confidence: 99%